Varstvo pravic davčnih zavezancev za DDV v Listini EU o temeljnih pravicah - Bartol Lesar, Mojca (Javna uprava, 2021)
The Charter of Fundamental Rights has been part of EU primary law since 2009. Its provisions are addressed to the institutions, bodies, offices and agencies of the Union with due regard for the principle of subsidiarity and to the Member States only when they are implementing Union law. The author demonstrates that the Charter is also applicable in the area of value-added tax (VAT), as Member States enforce Union law in the implementation of the taxation with VAT. Therefore, the protection of rights under the Charter is also relevant for VAT taxable persons. In the field of VAT, tax administrations, courts and taxable persons need to respect and know the substantive provisions of the VAT Directive and the related case-law of the Court of Justice of the EU (CJEU), as well as domestic substantive and procedural rules and case-law. All this is complex and, therefore, demanding for the participants in the procedure, which allows for a wide range of possible violations of the fundamental rights of taxable persons. Based on a review of the CJEU case-law, the author finds that judgments concerning VAT in connection with the Charter are scant, and demonstrates that the provisions of the Charter are relevant not only in substantive but also in minor offences and criminal matters regarding VAT, although the latter do not constitute an implementation of EU law.
Keywords: Charter of Fundamental Rights of the EU; človekove pravice; davčni postopek; davčni zavezanec; davčno pravo; davek na dodano vrednost (DDV); davki; human rights; Listina EU o temeljnih pravicah; oprostitev DDV; right to an effective legal remedy; tax procedure; taxable person; taxes; value added tax (VAT); VAT exemption